Imagine Yourself Dancing Waltz: The Effect of Imagination on Memory in Alzheimer’s Disease - El Haj, Mohamad; Robin, Frédérique; Moustafa, Ahmed A.; Gallouj, Karim (Current Alzheimer Research, 2023)
Background: Self-imagination refers to a mnemonic strategy of imagining oneself at a scene related to a cue. Objective: We tested the effect of self-imagination on memory recall in Alzheimer’s disease (AD) Methods: Individuals with AD and healthy controls were invited to perform two conditions. In the control (i.e., semantic elaboration) condition, participants were asked to define to which semantic category (e.g., dance) words (e.g., waltz) belong. However, in a self-imagining condition, participants were asked to imagine themselves in a scene related to the stimuli (e.g., dancing waltz). Both conditions were followed by two free memory tests with two different intervals (20 seconds vs. 20 minutes). Results: Analysis showed a beneficial effect of self-imagination for the 20-second but not for the 20- minute recall in AD participants and controls. Conclusion: Clinicians can incorporate our findings when assessing, especially when trying to rehabilitate, episodic memory in AD.
Keywords: imagination